Gestión administrativa en el Comercial Variedades 1 en la ciudad de Babahoyo - Arias Torres, Stalin Vicente (2020)
The Comercial Variedades 1 is located on 10 de Agosto Street between Pedro Carbo and Juan Montalvo of the Babahoyo canton, a private institution dedicated to the marketing of white goods such as; household appliances and furniture in general, sales are; cash, credit and cumulative plan with cash price, which works as the parent company of Comercial Variedades 2, a branch that is located on Calle 5 de Junio between Pedro Carbo and Juan Montalvo, the current Administrator is Lcda. Gabriela Almache. The case study is carried out in order to determine what are the factors causing the problems that have arisen in the Commercial Varieties in recent years, since the Lcda. Gabriela Almache took office, the current administrator is the daughter of Lcdo. Manuel Almache, former manager and owner of the branch, Comercial Variedades 2, said factors influence sales levels; the absence of sales experience, lack of knowledge in business administration and strategy implementation, are fundamental factors to be competitive in today's market. The objective of the present case is to make known which are the problems that affect the Administrative Management of the company, it presents several problems such as; lack of quality control, manual sales record (does not use electronic systems for sales record), lacks advertising strategies (does not use different advertising media), disorder in the warehouse area (the mattress line is not found in a proper order or classification), delay of the merchandise (the merchandise does not usually arrive in the time requested by customers), lack of sales training (the seller is not trained by an internal manager or an external institution), lack of security implements (in the unloading of the merchandise that arrives) lack of adaptation in the infrastructure (failures or cracks in some parts of the infrastructure). The methodology applied in the present case study was descriptive research, and the techniques used were the interview, direct observation, and survey, which provide timely and accurate information about the company